Identification of Nitrogen Starvation-Responsive MicroRNAs in Arabidopsis thaliana - Liang, Gang; He, Hua; Yu, Diqiu (PLOS ONE, 2012)
microRNAs (miRNAs) are a class of negative regulators that take part in many processes such as growth and development, stress responses, and metabolism in plants. Recently, miRNAs were shown to function in plant nutrient metabolism. Moreover, several miRNAs were identified in the response to nitrogen (N) deficiency. To investigate the functions of other miRNAs in N deficiency, deep sequencing technology was used to detect the expression of small RNAs under N-sufficient and -deficient conditions. The results showed that members from the same miRNA families displayed differential expression in response to N deficiency. Upon N starvation, the expression of miR169, miR171, miR395, miR397, miR398, miR399, miR408, miR827, and miR857 was repressed, whereas those of miR160, miR780, miR826, miR842, and miR846 were induced. miR826, a newly identified N-starvation-induced miRNA, was found to target the AOP2 gene. Among these N-starvation-responsive miRNAs, several were involved in cross-talk among responses to different nutrient (N, P, S, Cu) deficiencies. miR160, miR167, and miR171 could be responsible for the development of Arabidopsis root systems under N-starvation conditions. In addition, twenty novel miRNAs were identified and nine of them were significantly responsive to N-starvation. This study represents comprehensive expression profiling of N-starvation-responsive miRNAs and advances our understanding of the regulation of N homeostasis mediated by miRNAs.